2015
DOI: 10.3390/app5041221
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ta2O5 and Nb2O5 Dopants on the Stable Dielectric Properties of BaTiO3–(Bi0.5Na0.5)TiO3-Based Materials

Abstract: Abstract:In this study, BaTiO3-(Bi0.5Na0.5)TiO3 ceramics with various amounts of Ta2O5 dopant were investigated for their ability to enhance high-temperature stability to meet X9R specifications. The results were compared to those for ceramics with the common Nb2O5 additive. The best composition appeared to be 0.9BaTiO3-0.1(Bi0.5Na0.5)TiO3 with 2 mol% Ta2O5 dopant sintered at 1215 °C, which had a dielectric constant of 1386, a tanδ value of 1.8%, temperature coefficients of capacitance (TCCs) of −1.3% and 1.2%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 24 publications
0
3
0
1
Order By: Relevance
“…Many studies have shown that adding a small amount of Nb 2 O 5 can suppress the dielectric peak of BNT-based ceramics and shift T m downward to low temperature, achieving TCC ± 0.15 standard in a wide temperature range. [35][36][37][38][39][40][41] Based on the above considerations, it is logical to explore Nb 2 O 5 addition in our previous optimized Ce 4+ -doped BNBST ceramics for boosting dielectric temperature stability and energy storage properties. x wt%Nb 2 O 5 , x = 0, 0.5, 1.0, 1.5, 2.0, 2.5, 3.0, 3.5, and 4.0) ceramics by a solid-state reaction method.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have shown that adding a small amount of Nb 2 O 5 can suppress the dielectric peak of BNT-based ceramics and shift T m downward to low temperature, achieving TCC ± 0.15 standard in a wide temperature range. [35][36][37][38][39][40][41] Based on the above considerations, it is logical to explore Nb 2 O 5 addition in our previous optimized Ce 4+ -doped BNBST ceramics for boosting dielectric temperature stability and energy storage properties. x wt%Nb 2 O 5 , x = 0, 0.5, 1.0, 1.5, 2.0, 2.5, 3.0, 3.5, and 4.0) ceramics by a solid-state reaction method.…”
Section: Introductionmentioning
confidence: 99%
“…However, its relatively low recoverable energy density ( W rec ∼ 1.15 J/cm 3 ) needs to be further increased, and the window of temperature stability also needs to be further widened. Many studies have shown that adding a small amount of Nb 2 O 5 can suppress the dielectric peak of BNT‐based ceramics and shift T m downward to low temperature, achieving TCC ± 0.15 standard in a wide temperature range 35–41 . Based on the above considerations, it is logical to explore Nb 2 O 5 addition in our previous optimized Ce 4+ ‐doped BNBST ceramics for boosting dielectric temperature stability and energy storage properties.…”
Section: Introductionmentioning
confidence: 99%
“…Electronic properties of ceramics have put them on the top of the materials used for sensors, actuators, capacitors and other parts integrated in electronic devices [1][2][3][4]. Ferroelectric perovskite ceramics have been intensively studies over the years, from a macro towards a nano-scale approach [5][6][7][8]. Multilayer ceramic capacitors (MLCC) have enabled tailoring of the properties by the modification of ceramic layer and the interface between them, which further led to the production of high capacitance and stability capacitors [9].…”
Section: Introductionmentioning
confidence: 99%
“…Quando dopado com óxidos metálicos a sua constante dielétrica tende a se elevar em ordens de 10³ a 10 5 (Luoa et al, 2018) e a sua resistividade elétrica tende a diminuir para ordens entre 10 e 10 4 .cm, podendo, desta forma, exercer características de material semicondutor (Cheng, 1989;Pu et al, 2005;Gheno et al, 2007) Óxidos da família perovskita são amplamente utilizados na indústria de eletrocerâmicos, eletroeletrônicos, eletromecânicos e eletro-ópticos (Al-Shakarchi, 2010;López-Joárez et al, 2011;Asimalopoulos et al, 2014). O titanato de bário, por ser um material ferroelétrico com alta constante dielétrica em temperatura ambiente, é bastante utilizado na fabricação de capacitores multicamadas, termistores com coeficientes de temperatura positiva (PTCs), transdutores piezoelétricos e uma variedade de dispositivos ópticos (Wang et al, 2015;Mancini e Filho, 2007).…”
Section: Introductionunclassified